Antioxidant study of different parts of stink bean (Parkia Speciosa) and its effect on the oxidative stability of beef patty / Nur Syahirah Yahaya, Nina Naquiah Ahmad Nizar and Marina Zulkifli - Yahaya, Nur Syahirah; Ahmad Nizar, Nina Naquiah; Zulkifli, Marina (Universiti Teknologi MARA, Negeri Sembilan, 2023)
This study investigated the potential of stink bean leaves and peels as natural antioxidants in meat products. The leaves and peels were extracted using water as a solvent. Antioxidant analysis that includes Total Phenolic Compound (TPC), Free Radical Scavenging Activity (DPPH) and Ferric Reducing Antioxidant Power (FRAP) assays were carried out to determine the total polyphenols and antioxidant activities in both extracts. TPC was determined using Follin-Ciocalteu reagent and the result indicated that TPC for peel extract was 37.51 mg GAE/g and 3.95 mg GAE/g for leaf extract. The antioxidant activities were compared with synthetic antioxidant which was ascorbic acid. For DPPH, scavenging effects of extracts and ascorbic acid decreased significantly in the order of ascorbic acid, peel extract, and leaf extract with the percentage of 94.93%, 93.64% and 90.35%, respectively at 1000 ppm. Meanwhile for FRAP assay, peel extract at 200 ppm and leaf extract at 800 ppm were comparable to 600 ppm of ascorbic acid. Thus, 200 ppm of peel extract was chosen to be incorporated into beef patty and be compared with ascorbic acid at 600 ppm. Oxidation analysis was performed on beef patties that were prepared using three formulas which were sample without the addition of extract (control), sample with ascorbic acid and sample with peel extract. Lipid oxidation analysis was performed by determining the peroxide value (PV) which varied from 5.89 to 7.56 meq/kg at the end of the storage. Hence, both parts of plants showed antioxidants properties, but peel extract was proven to possess higher antioxidant activity and has a potential to be incorporated into beef patty and as natural antioxidant.